Positive behaviour support for challenging behaviour after acquired brain injury: An introduction to PBS + PLUS and three case studies. Issue 1 (2nd January 2021) - Gould, Kate Rachel; Ponsford, Jennie Louise; Hicks, Amelia J.; Hopwood, Malcolm; Renison, Belinda; Feeney, Timothy J.
ABSTRACT: Challenging behaviours are a common and distressing consequence of acquired brain injury (ABI). There are no evidence-based guidelines for managing challenging behaviours after ABI, leaving clinicians with few resources to guide practice. Findings from case studies and single-subject experimental designs support the use of positive behaviour support (PBS) interventions for challenging behaviour post-ABI. This paper introduces PBS + PLUS: a multi-component and flexible PBS intervention using a person-driven collaborative approach to build a meaningful life and self-regulate behaviour after ABI. PBS + PLUS is currently being examined in a randomized controlled trial (RCT). Three detailed pilot case studies illustrate the highly individualized implementation of the programme, delivered to the individuals with ABI and carers over 12 months by a transdisciplinary team including neuropsychologists, occupational therapists, and psychiatrists. Objective behavioural outcomes are reported for participants using the Overt Behaviour Scale at baseline and four-monthly intervals for two years. Goal attainment scaling was used to measure personally meaningful goals. The qualitative appraisals of the intervention by participants, families and carers, and 12-month follow-up outcomes are described. The advantages and challenges of programme delivery are discussed. These case studies will assist clinicians and service providers to implement PBS + PLUS in anticipation of the results of the RCT.